1968
DOI: 10.1136/bmj.4.5628.430
|View full text |Cite
|
Sign up to set email alerts
|

Counteraction of Platelet Activity at Sites of Laser-induced Endothelial Trauma

Abstract: . med. J3., 1968, 4, 430-431 : ummary: The effects of dextran 70 (Mw 70,000; Macrodex), heparin, dipyridamole (Persantin), and prostaglandin E1 on the behaviour of platelets were investigated at sites of endothelial trauma induced with a ruby biolaser in arterioles in the rabbit ear chamber. This technique has several advantages over previous methods of studying platelet activity.Dextran 70 (2 g./kg. body weight) caused a profound reduction in platelet activity four to six hours after its administration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1
1

Year Published

1974
1974
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 6 publications
(9 reference statements)
3
16
1
1
Order By: Relevance
“…This find ing is in accordance with results reported by several other investigators [2,7,10,12,13,15] while some authors reported negative re sults [16,[18][19][20], These controversial find ings may be explained by the different exper imental models used and also by the different ways to interpret the results. So, if thrombus formation is evaluated during the first min utes after the vascular lesions, dipyridamole is usually markedly effective [2,7,10,12,13,15], while in models in which the thrombi are evaluated a longer time after their origin (usually hours) ASA has been found to be more effective than dipyridamole [16,[18][19][20], 10 mg dipyridamole/kg were less effec tive if administered intravenously. Here the antithrombotic effect was tested 30 min after injection compared to 90-120 min after oral application.…”
Section: Discussionsupporting
confidence: 80%
“…This find ing is in accordance with results reported by several other investigators [2,7,10,12,13,15] while some authors reported negative re sults [16,[18][19][20], These controversial find ings may be explained by the different exper imental models used and also by the different ways to interpret the results. So, if thrombus formation is evaluated during the first min utes after the vascular lesions, dipyridamole is usually markedly effective [2,7,10,12,13,15], while in models in which the thrombi are evaluated a longer time after their origin (usually hours) ASA has been found to be more effective than dipyridamole [16,[18][19][20], 10 mg dipyridamole/kg were less effec tive if administered intravenously. Here the antithrombotic effect was tested 30 min after injection compared to 90-120 min after oral application.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings that SCIP conversion leads to down-regulation of platelet surface adhesiveness may provide a partial explanation for previous observations that platelets in direct contact with exposed subendothelium eventually become non-reactive toward other platelets (40,45,46). Given the central role played by integrin ␣ IIb b 3 in hemostasis and thrombogenesis, unraveling the molecular mechanisms utilized by FXIII and calpain to regulate integrin ␣ IIb b 3 receptor function may have pathophysiological importance.…”
Section: Discussionsupporting
confidence: 46%
“…This was expected since the major effect of heparin is on clotting factors (i.e., anticoagulation) rather than on platelet aggregation per se. In fact, Arfors et al, 18 Honour and Mitchell, 2 and Born and Philp 3 also failed to demonstrate an effect of heparin on either laser-induced or mechanically induced aggregates in rabbit ear chambers or rabbit pial vessels.…”
Section: Effects Of Other Drugs and Localization Of Drug Effectmentioning
confidence: 97%